A case report of food-dependent exercise-induced anaphylaxis (FDEIA) treated with omalizumab - Mohamed, Sara; Thalappil, Sherin; Mohamed Ali, Ramzy (Frontiers in Allergy, 2024)
Food-dependent exercise-induced anaphylaxis (FDEIA) is a rare and complex clinical condition in which allergic reactions are triggered by specific foods combined with physical activity, even though the food allergen and exercise are tolerated individually. Wheat is the most common culprit food leading to wheat dependent exercise induced anaphylaxis (WDEIA). Management of FDEIA is challenging due to the unpredictability of attacks and the lack of approved prophylactic medications. This report presents a case of successful symptom control in a young woman with WDEIA through the addition of omalizumab to the treatment regimen. To our knowledge, this is the first reported case of food-dependent exercise-induced anaphylaxis (FDEIA) treated with omalizumab as the primary indication. We also summarize the pathophysiology, diagnosis and treatment of FDEIA. The need for heightened awareness and innovative therapeutic approaches is crucial for those affected by FDEIA.